(untitled) (European Journal of Behavioral Sciences, 2025)
The study examines the psychological and economic well-being of sewage workers in Gurugram through a quantitative approach with special emphasis on the health vulnerabilities they are exposed to. The paper aims to shed light on the problems faced by workers and their impact on workers’ well-being. The study utilises a mixed methods approach including quantitative surveys and personal interviews. A total of 100 sewage workers were surveyed. The study used the following scales: Hamilton Anxiety scale, Occupational Stress scale, WHOQOL BREF, Financial Well-being scale, and Knowledge about Health Risks scale. The data collected through the survey was used to conduct statistical tests like ANOVA, correlation, and regression. In addition to the surveys, 12 respondents were also interviewed, and their responses were thematically analysed. The study found that expenditure had a significant positive correlation with anxiety and a significant negative correlation with quality of life and financial well-being. Meanwhile, anxiety had a significant negative correlation with quality of life and financial well-being, and vice versa. Furthermore, it was found that most of the workers interviewed believed that schemes or savings accounts provide no help or benefit to unorganised workers, attempted to get a loan but had been denied one, and experienced significant stress and suffered from physical injuries while refusing to seek professional help due to the increased cost. Using quantitative and qualitative analysis tools, the study was able to better determine and understand the state of the workers while increasing awareness about the obstacles faced by them.